2021
DOI: 10.3390/ma14185334
|View full text |Cite
|
Sign up to set email alerts
|

A Closer Look on Nuclear Radiation Shielding Properties of Eu3+ Doped Heavy Metal Oxide Glasses: Impact of Al2O3/PbO Substitution

Abstract: In this study, a group of heavy metal oxide glasses with a nominal composition of 55B2O3 + 19.5TeO2 + 10K2O + (15−x) PbO + xAl2O3 + 0.5Eu2O3 (where x = 0, 2.5, 5, 7.5, 10, 12.5, and 15 in wt.%) were investigated in terms of their nuclear radiation shielding properties. These glasses containing lanthanide-doped heavy metal oxide were envisioned to yield valuable results in respect to radiation shielding, and thus a detailed investigation was carried out; the obtained results were compared with traditional and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…In addition, the density and radiation-shielding ability of glass can be significantly improved by doping various heavy metal elements (such as Bi, Pb, Ba, and Gd). Many research groups have reported on glass of various substrates and their nuclear protective properties in the literature [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the density and radiation-shielding ability of glass can be significantly improved by doping various heavy metal elements (such as Bi, Pb, Ba, and Gd). Many research groups have reported on glass of various substrates and their nuclear protective properties in the literature [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The cost, noncorrosive, eco-friendly properties, high transparency, non-toxic nature, and good mechanical features are the advantages of using glasses as shielding materials. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Researches show that tellurite glass is extremely effective against gamma photon in comparison with the other types of glasses. [20][21][22][23] Sayyed [22] surveyed the effect of the Bi 2 O 3 on the shielding ability of the tellurite glass with the general formula of TeO 2 -B 2 O 3 -ZnO.…”
Section: Introductionmentioning
confidence: 99%